2001
DOI: 10.1038/sj.cdd.4400825
|View full text |Cite
|
Sign up to set email alerts
|

The CD7− subset of CD4+ memory T cells is prone to accelerated apoptosis that is prevented by interleukin-15 (IL-15)

Abstract: The CD7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Our data indicate that oxidative stress-mediated apoptosis induced by H 2 O 2 was more prominent in T cells cultured with IL-2 than in those cultured with IL-15 ( Figure 1A). These results are similar to those shown by earlier studies highlighting anti-apoptotic characteristic of IL-15 [25-27]. However, we reasoned that for an oxidative agent such as H 2 O 2 to induce cell death differentially, differences must exist in reduced or oxidized surface molecules/proteins which could correlate to the cytokines used for pretreatment and hence the difference in susceptibility to H 2 O 2 -mediated apoptosis.…”
Section: Resultssupporting
confidence: 90%
“…Our data indicate that oxidative stress-mediated apoptosis induced by H 2 O 2 was more prominent in T cells cultured with IL-2 than in those cultured with IL-15 ( Figure 1A). These results are similar to those shown by earlier studies highlighting anti-apoptotic characteristic of IL-15 [25-27]. However, we reasoned that for an oxidative agent such as H 2 O 2 to induce cell death differentially, differences must exist in reduced or oxidized surface molecules/proteins which could correlate to the cytokines used for pretreatment and hence the difference in susceptibility to H 2 O 2 -mediated apoptosis.…”
Section: Resultssupporting
confidence: 90%
“…6 However, our in vivo studies identified a lack of FOXP3+ cells in SS and therefore excluded the use of FOXP3 as a possible tumour cell marker in SS. 7 Other groups have identified Sézary cells by loss of CD7 8,9 or CD26. [10][11][12][13] However, loss of CD26 is seen in only about half of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cells of the population CD7 ) from the peripheral blood of all Se´zary syndrome patients are resistant to galectin-1-induced apoptosis. Thus, resistance of CD7 ) T cells to galectin-1-induced apoptosis may contribute to the accumulation of CD7 ) Se´zary T cells during progression of the disease [58,82].…”
Section: Cd7mentioning
confidence: 97%